The Role of Effort in Perceiving Distance - Proffitt, Dennis R.; Stefanucci, Jeanine; Banton, Tom; Epstein, William (Psychological Science, 2003)
Berkeley proposed that space is perceived in terms of effort. Consistent with his proposal, the present studies show that perceived egocentric distance increases when people are encumbered by wearing a heavy backpack or have completed a visual-motor adaptation that reduces the anticipated optic flow coinciding with walking effort. In accord with Berkeley's proposal and Gibson's theory of affordances, these studies show that the perception of spatial layout is influenced by locomotor effort.